Nesfatin-1: current status as a peripheral hormone and future prospects. (December 2016) - Prinz, Philip; Stengel, Andreas
Highlights: Nesfatin-1 is a well-established central inhibitor of food intake. NUCB2/nesfatin-1 exerts pleiotropic actions in the periphery. Involved in glucose and lipid metabolism, cardiovascular and reproductive functions. Nesfatin-1 is a potential drug target for diabetes and fatty liver disease. Abstract : This review summarizes current data focusing on the peripheral effects of NUCB2/nesfatin-1 including the regulation of food intake, glucose homeostasis, lipid metabolism, cardiovascular effects and reproductive functions as well as its possible involvement in psychological disorders. Additionally, we will highlight gaps in knowledge in order to stimulate further research. Lastly, we will give an outlook on potential therapeutic implications of this pleiotropic peptide.